Assessment Of Genetic Relatedness Among Hydrilla Verticillata (L. F.) Royle Accessions In Malaysia Using RAPD And AFLP Markers - Chin, Choke Lin (2010)
Genetic relationships among 119 accessions of Hydrilla verticillata from 28 locations in Malaysia were determined using Random Amplified Polymorphic DNA (RAPD) and 82 accessions of H. verticillata from 26 locations were studied using the Amplified Fragment Length Polymorphism (AFLP) technique. A total of nine RAPD primers produced 143 amplified fragments with 105 of them were polymorphic. RAPD data used to generate a Neighbour-Joining tree and Principal Coordinate Analysis (PCO) clustered these accessions into four groups that did not separate them according to geographical areas.